2021
DOI: 10.1002/bbb.2290
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis on potential uses of brewer's spent grains in a biorefinery for the circular economy transition of the beer industry

Abstract: This comprehensive review aims to elucidate the state of the art related to research trends regarding the use of brewer's spent grains (BSG), the main solid by-product generated in breweries. Its status, future opportunities, and emerging trends were evaluated by bibliometric analysis, which contributed to clarifying the knowledge and perspectives in the field. In total, 510 documents were obtained from the Web of Science© database in a timespan from 1900 to 2020. VosViewer software and R-bibliometrix package … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 103 publications
(258 reference statements)
1
21
0
1
Order By: Relevance
“…Bibliometrics is an important tool for determining research trends. Studies with bibliometrics have been conducted in various fields; for instance, in engineering on soil erosion modeling [12] and industrial waste water treatment [13], on circular economy in the building and construction sector [14], and an analysis of the potential uses of brewer's spent grains in a biorefinery for the circular economy transition [15]. In energy and environment, bibliometric analysis has presented research trends in biomass and biofuels [16,17], energy security [18], nuclear energy research [19], and energy research trends from specific geographic locations [20,21], and in social science [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics is an important tool for determining research trends. Studies with bibliometrics have been conducted in various fields; for instance, in engineering on soil erosion modeling [12] and industrial waste water treatment [13], on circular economy in the building and construction sector [14], and an analysis of the potential uses of brewer's spent grains in a biorefinery for the circular economy transition [15]. In energy and environment, bibliometric analysis has presented research trends in biomass and biofuels [16,17], energy security [18], nuclear energy research [19], and energy research trends from specific geographic locations [20,21], and in social science [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of bibliometric analysis, recent studies demonstrated that this approach could be a strategy to evaluate the research trends and gaps in science 1,2,36–38 . In general, bibliometric analysis can be defined as an evaluation of scientific production through studies of observable parameters, such as published journals, books, authors, keywords and citations 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Through bibliometric analysis, trends and perspectives in the field can be highlighted to solve industrial problems and support decision‐making in science 40 . For instance, in the areas of bio‐waste, 41 energy recovery from macaúba husk, 1 the valorization of orange industrial waste, 37 the valorization of brewer's spent grains, 36 anaerobic digestion technology, 42 biodiesel production 43 and enzyme immobilization, 44 bibliometrics has identified the knowledge gaps and elucidated the establishment of future studies to better understand the state of the art in the research field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values are expressed as a percentage of dry matter (% DM ), or with an appropriate unit of measurement, with indicated standard deviations.while through integrated biorefinery processes, multiple end products could be produced. However, to meet the sustainability requirements, development and implementation of sustainable technologies in conversion of BSG and other lignocellulosic materials into bio-basaed products are urgently needed(Sganzerla et al, 2021a) Sganzerla et al (2021b). made techno-economic assessment of bioenergy and fertilizer production by anaerobic digestion of BSG with simulations performed by integrating the production of biomethane, electricity, thermal energy, and fertilizer, which is one of examples of application of brewer's spent grains following biorefinery concept.…”
mentioning
confidence: 99%